Time-dependent, patient-centered perceptions of quality measures for total joint arthroplasty: a cross-sectional, choice modeling study - Jacie L. Lemos; Jessica M. Welch; Derek F. Amanatullah; Lauren M. Shapiro; Alex H. S. Harris; Robin N. Kamal (BMC Musculoskeletal Disorders)
Abstract Background As value-based care arrangements continue to assess quality of care and costs, comprehensive and patient-centered definitions of quality of care are required. While patient-reported outcome measures are increasingly integrated into quality assessments following total joint arthroplasty (TJA), patient perceptions of quality paired with the phase of surgical care has not been described. The purpose of this study was to assess how TJA patients perceive measures of quality of care and assess if these perceptions change based on the phase of care. Methods Patients who had undergone a TJA within the past two years or had a scheduled TJA within the next 6 months completed a questionnaire designed using best-worst scaling, a method used to measure individuals’ priorities by asking participants to make repeated selections of the best and worst items in a series of subsets of items. Subanalyses were calculated to compare each phase of care (preoperative, short term postoperative, and long term postoperative). Results A total of 153 patients completed the questionnaire; 36 were preoperative, 55 were short term postoperative, and 62 were long term postoperative. Patients placed the highest value on improving activities of daily living (β = 1.03, CI = 0.90-1.16), decreasing pain (β = 0.65, CI = 0.53-0.76), and avoiding re-intervention (β = 0.64, CI = 0.52-0.76). Decreasing pain ranked as a higher priority preoperatively compared to short term postoperatively, and subsequently increased in priority again after 6 months. Avoiding reintervention was less important to patients preoperatively compared to postoperatively. Avoiding complications was more important to patients preoperatively compared to postoperatively. Conclusions Matching outcome assessments with how patients assess their quality of care throughout the TJA recovery process can inform phase-specific quality improvement initiatives and value definitions. Activities of daily living should be measured across phases of care and into long-term recovery. TJA value dashboards should align with these patient-driven perceptions of quality. Level of evidence Level III, cohort study.